2017
DOI: 10.1128/aem.01251-17
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure and Substrate Specificity Modification of Acetyl Xylan Esterase from Aspergillus luchuensis

Abstract: Acetyl xylan esterase (AXE) catalyzes the hydrolysis of the acetyl bonds present in plant cell wall polysaccharides. Here, we determined the crystal structure of AXE from (AXEA), providing the three-dimensional structure of an enzyme in the Esterase_phb family. AXEA shares its core α/β-hydrolase fold structure with esterases in other families, but it has an extended central β-sheet at both its ends and an extra loop. Structural comparison with a ferulic acid esterase (FAE) from indicated that AXEA has a conser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 58 publications
0
27
0
Order By: Relevance
“…Recent studies have shown carboxylesterase activity in Penicillium chrysogenum, whereby the activity was found to be 5.4 U/L [54], with Aspergillus and Trichoderma sp. being other organisms that were reported for carboxylesterase activity [55]. This illustrated the capability of the N. mirabilis pods' digestive fluids to hydrolyse acetyl groups including those associated with xylan.…”
Section: Biophysico-chemical Characteristics Of the N Mirabilis Digementioning
confidence: 63%
See 1 more Smart Citation
“…Recent studies have shown carboxylesterase activity in Penicillium chrysogenum, whereby the activity was found to be 5.4 U/L [54], with Aspergillus and Trichoderma sp. being other organisms that were reported for carboxylesterase activity [55]. This illustrated the capability of the N. mirabilis pods' digestive fluids to hydrolyse acetyl groups including those associated with xylan.…”
Section: Biophysico-chemical Characteristics Of the N Mirabilis Digementioning
confidence: 63%
“…Furthermore, Bacillus sp., in particular, B. vallismortis, was confirmed to have the ability to produce short-chained acetyl xylan esterases [56]. The decoupling of the xylan backbone is highly dependent on the endo/β-xylosidases; albeit acetyl xylan esterases, including xylanases, are largely involved [55]. By reducing the acetyl groups, the endo-xylanases will, thus, be effective during the hydrolysis of mixed agro-waste [30], furthering the decomposition of xylan to xylose.…”
Section: Biophysico-chemical Characteristics Of the N Mirabilis Digementioning
confidence: 99%
“…Homology modeling was performed based on a template structure with high sequence identity. In particular, the tannase-related SF1-3 FAEs showed high homology with the FAE B (AoFaeB) from Aspergillus oryzae [33] while SF6 acetyl xylan related-FAEs showed homology with an acetyl xylan esterase from Aspergillus luchuensis [34]. The SF5 acetyl-xylan-related FAEs showed no significant homology with determined structures (<30%), therefore, this intriguing group was not used for the prediction of surface properties and SMD simulations.…”
Section: Factors Affecting Transesterificationmentioning
confidence: 99%
“…It is distantly related to the other fungal CE1 members (Esterase, PHB depolymerase, IPR010126), but related to the Esterase D/S-formylglutathione hydrolase sequences (IPR014186) according to InterPro classification [22]. In comparison with bacterial CE1 enzymes, fungal CE1 enzymes mainly belong to the Esterase_phb family based on the ESTHER database, a classification for proteins with an α/β-hydrolase fold [23], which is distantly related to bacterial enzymes belonging to Antigen85c family (<20% sequence identity) [24]. Thus far, two crystal structures of fungal CE1 enzymes have been reported, i.e.…”
mentioning
confidence: 99%
“…Anaeromyces mucronatus AmCE1 (PDB: 5CXU [25]) and Aspergillus luchuensis AlAXEA (formerly Aspergillus awamori) (PDB: 5X6S [24]).…”
mentioning
confidence: 99%